A randomized trial of direct pulp capping in primary molars using MTA compared to 3Mixtatin: a novel pulp capping biomaterial. Issue 4 (15th September 2015) - Asl Aminabadi, Naser; Satrab, Soheil; Najafpour, Ebrahim; Samiei, Mohammad; Jamali, Zahra; Shirazi, Sajjad
Abstract : Objective: This study aimed to examine the efficacy of 3Mixtatin (a combination of simvastatin and 3Mix antibiotic) as a novel pulp capping biomaterial in DPC of human primary molars. Methods: In this randomized clinical trial, 160 primary molars from 83 healthy children aged 3–6 years were randomly allocated into four groups. Small traumatic non‐caries pulpal exposures were treated by DPC using simvastatin, 3Mix, 3Mixtatin, or MTA. Capping materials were covered with hard‐setting zinc oxide eugenol (ZOE) cement, and then, teeth were restored with amalgam. Clinical and radiographic examinations were conducted at 2, 6, and 12 months after treatment. The data were compared using chi‐square test at a significance level of 0.05. Results: One hundred and twenty‐nine teeth were available for follow‐up study. By the end of 12 months, the overall success rates were 93.8% in MTA, 91.9% in 3Mixtatin, 62.5% in 3Mix, and 57.1% in simvastatingroups. No statistically significant difference was found between the outcomes of MTA and 3Mixtatin groups ( P > 0.05). 3Mixtatin had statistically superior results compared to 3Mix and simvastatin ( P < 0.01). Conclusion: Radiographic and clinical outcomes in 3Mixtatin group could suggest it as an acceptable alternative in DPC of primary molar teeth.